2019
DOI: 10.1108/ijbm-01-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of credit card spending and debt of Chinese consumers

Abstract: Purpose The rapid growth of credit card use in China poses the potential for card overuse and the accumulation of increased debt. The purpose of this paper is to report on an investigation into the determinants of overall credit card spending and card-financed debt by Chinese consumers. Design/methodology/approach This study focusses on two dependent variables: credit card monthly spending and card debt. The spending measure is based on consumer outlay for the month preceding the survey. Card debt is the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
48

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(81 citation statements)
references
References 49 publications
1
32
0
48
Order By: Relevance
“…Allgood and Walstad (2013); Barboza et al. (2017); Lin, Revindo, Gan, and Cohen (2019) and Mottola (2013) show that these variables may have a bearing on credit card repayment behaviour. In line with Barboza et al.…”
Section: Methodsmentioning
confidence: 99%
“…Allgood and Walstad (2013); Barboza et al. (2017); Lin, Revindo, Gan, and Cohen (2019) and Mottola (2013) show that these variables may have a bearing on credit card repayment behaviour. In line with Barboza et al.…”
Section: Methodsmentioning
confidence: 99%
“…Demographic factors also significantly influence the tendency to overindebtedness. Lin et al (2019) found that men are more favorable to debt than women. In the age terms, young people under 30 are more disrespectful of debt compared to people over 45 (Keese 2012;Sevim et al 2012).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Moreover, risk perception differs based on individual occupations, income, religion, marital status, and level of education (Keese 2010). Ponchio (2006) and Lin et al (2019) focused on the relationship between demographic factors and debt, and identified that men are not more favorable to debt than women are. Younger people tend to perceive their debt burden as significantly lower, whereas those over 45 years are more likely to have a higher debt (Daud et al 2019;Keese 2010).…”
Section: Theoretical Basismentioning
confidence: 99%